Direct Dehydroxytrifluoromethoxylation of Alcohols. (7th December 2017) - Jiang, Xiaohuan; Deng, Zhijie; Tang, Pingping
Abstract: The first example of a direct dehydroxytrifluoromethoxylation of alcohols has been developed. This method generated an alkyl fluoroformate in situ from alcohols, followed by nucleophilic trifluoromethoxylation with trifluoromethyl arylsulfonate (TFMS) as the trifluoromethoxylation reagent. The reaction is operationally simple and scalable, and it proceeds under mild reaction conditions to provide access to a wide range of trifluoromethyl ethers from alcohols. In addition, this method is suitable for the late‐stage trifluoromethoxylation of complex small molecules.